Role of MOTS-c in the regulation of bone metabolism - Yi, Xuejie; Hu, Guangxuan; Yang, Yang; Li, Jing; Jin, Junjie; Chang, Bo (Frontiers in Physiology, 2023)
MOTS-c, a mitochondrial-derived peptide (MDP) targeting tissues and organs, is an essential regulatory mediator of cell protection and energy metabolism and is involved in the development of specific diseases. Recent studies revealed MOTS-c promotes osteoblasts proliferation, differentiation, and mineralization; furthermore, it inhibits osteoclast production and mediates bone metabolism and bone reconstruction regulation. Exercise effectively upregulates MOTS-c expression in bones; however, the exact mechanism is unclear. Therefore, this article reviewed the tissue distribution and function of MOTS-c, engaged the latest research development in the regulation of osteoblasts and osteoclasts, and revealed the potential molecular mechanisms of exercise in the regulation of bone metabolism to provide a theoretical reference for establishing methods and means to prevent and treat skeletal metabolic diseases by exercise.